Urban family ties and household latrines in rural India: A cross-sectional analysis of national data. - Anna Lunn (PLoS ONE)
Access to toilets and latrines represents both a development indicator and a significant factor in child mortality and physical development. The lack of latrines in rural India therefore constitutes a major global health challenge. Given the urban-rural gap in latrine ownership across India, I investigated how family ties to major cities, which extend beyond the local community affected by neighbors' defecation practices, shaped latrine ownership in rural India. Using the national Rural Economic & Demographic Survey 2006 (n = 7,949), I analyzed the geographies of family ties, types of exchange and rural latrine ownership. Receiving family visits from major cities increased the likelihood of having a latrine (33% higher odds). The relationship between family visitors from major cities and rural latrine ownership was stronger for wealthier households (.031 increase in average marginal effect of urban visitors for a .5 standard deviation increase in household assets at the mean). Material support from family also increased the likelihood of latrine ownership (7.8% higher odds for each additional $200USD) suggesting that family members not living in major cities may still contribute necessary resources. The importance of personalized connections beyond the village, particularly to major cities, suggests that linking geographically disparate sanitation interventions may produce synergies.